MurA escape mutations uncouple peptidoglycan biosynthesis from PrkA signaling - Wamp, Sabrina; Rothe, Patricia; Stern, Daniel; Holland, Gudrun; Döhling, Janina; Halbedel, Sven (PLOS Pathogens, 2022)
Author summary Peptidoglycan (PG) is the main component of the bacterial cell wall and many of the PG synthesizing enzymes are antibiotic targets. We previously have discovered a new signaling route controlling PG production in the human pathogen Listeria monocytogenes. This route also determines the intrinsic resistance of L. monocytogenes against cephalosporins, a group of β-lactam antibiotics. Signaling involves PrkA, a membrane-embedded protein kinase, that is activated during cell wall stress to phosphorylate its target ReoM. Depending on its phosphorylation, ReoM activates or inactivates PG production by controlling the proteolytic stability of MurA, which catalyzes the first step in PG biosynthesis. MurA degradation depends on the ClpCP protease and we here have isolated murA mutations that escape this degradation. Using these mutants, we could show that regulation of PG biosynthesis through control of MurA stability is an important purpose of PrkA-mediated signaling in L. monocytogenes. Further experiments identified the transglycosylase RodA and the transpeptidase PBP B3 as additional downstream factors. Our results suggest that both proteins act together to translate the signals received by PrkA into adjustment of PG biosynthesis. These findings shed new light on the regulation of PG biosynthesis in Gram-positive bacteria with intrinsic β-lactam resistance.